POLA URUTAN FRASA PADA KLAUSA NOMINAL BAHASA INGGRIS DAN BAHASA INDONESIA - Dian Rivia Himmawati (Dinamika Bahasa dan Budaya, 2008)
Human language is rule-governed. But not all languages have the same exact rules. Sometimes the particular grammar in one language has to be governed but others do not have to.   Each of them has own characteristic even tough the phrase order among them is similar.   In general, the English and Indonesian phrase order is SVO or SPO (subject, Predicate, Object). But in noun clause English and Indonesian phrase order have different grammar.   Making equal sentences in Indonesian and English doesn’t always produce the same construction. It is related to the significance of each part to support the construction of clauses. And it can be used to describe the characteristic of each construction.  In noun clause the presence of particle in Indonesian phrase order makes the pattern of the phrase order change into P-S. And English phrase order is  so tight  that  the presence of particles in its grammar is unnecessary.   Key Words:  Phrase Order, Noun Clause, Particle